2021
DOI: 10.1186/s12886-021-01960-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and recurrence of pterygium in Saudi Arabia: a single center study with a long follow‐up

Abstract: Background This study described the clinical features of patients with pterygium and analyzed the recurrence rate of conjunctival autografting alone, conjunctival autografting combined with intraoperative mitomycin C, and amniotic membrane grafting. Methods A retrospective cohort study of primary pterygium was conducted between January 2017 and February 2020. Factors associated with pterygium severity and recurrence were analyzed by univariate anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Therefore, the existing surgical methods for pterygium still need to be continuously improved. Alsarhani et al [ 2 ] thought the double-sliding conjunctival flap surgery appeared to be a useful method, with a better success rate and lower pterygial recurrence in pterygium surgery. In particular, when pterygium is larger or a recurrent type, this technique can be easily cover the bare sclera, as compared to any transposition conjunctival flap operation [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the existing surgical methods for pterygium still need to be continuously improved. Alsarhani et al [ 2 ] thought the double-sliding conjunctival flap surgery appeared to be a useful method, with a better success rate and lower pterygial recurrence in pterygium surgery. In particular, when pterygium is larger or a recurrent type, this technique can be easily cover the bare sclera, as compared to any transposition conjunctival flap operation [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that the total number of pterygium in China is more than 100 million. Surgical excision is the only effective treatment for pterygium in clinic [ 2 ]. The commonly used surgical methods are based on the excision of pterygium, combined with conjunctival transplantation, amniotic membrane transplantation, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…This was related to the high incidence of this disease in hot climate countries. 28,29 This number of pterygium surgeries is an underestimate of the actual number because pterygium cases in our institution were also managed with conjunctival autografts. Different surgical modalities for pterygium excision were reported in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…Our finding is consistent with other findings in the region. 28 In corneal ulcers, we used the inlay-overlay combined method in all cases. Lacronaza et al, in their clinical series of AMT for corneal ulcers have adopted the same technique.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the efficacy of CAU is similar to that of LCAG for primary pterygium; however, the LCAG method carries the risk of corneal neovascularization at the site of autograft retrieval, which is not observed in CAU [ 41 ]. LCAG is also a longer and more technically difficult surgical method than CAU.…”
Section: Discussionmentioning
confidence: 99%